Child and adolescent mental health service provision: from group treatments for emerging personality disorders to clinician perspectives on implementing national referral criteria - Elders, Vera (The University of Edinburgh, 2017)
Background: During an age of fiscal constraint and increasing pressure to provide timely access to effective, efficient and evidence based care, there is an increased need for research to develop empirically based prevention and intervention strategies for complex psychological difficulties which often present during childhood and adolescence. Child and Adolescent Mental Health Services (CAMHS) are under significant pressure to deliver timely access to services, with demand frequently outstripping capacity to deliver. These challenges have highlighted the need for services to ensure that planning supports continued improvement in quality and delivers the best possible outcomes for service users. Systematic Review: A systematic review of the literature on the efficacy of group based interventions for adolescents with features or a diagnosis of Borderline Personality Disorder (BPD) was conducted. Seven articles met the inclusion criteria and underwent detailed quality analysis. All included studies reported a significant improvement in psychopathology and symptoms of distress as well as an improvement in quality of life for both group based interventions and treatment as usual. Overall, the results hold promise for current work with adolescents with BPD and highlight the importance for future research in this developing area. However, more rigorous research is required to identify the active ingredients of treatments for BPD in adolescents with a view to developing standardised treatment protocols. Empirical Study: A Delphi study was conducted to explore perceptions on the relevance, practicalities, importance and feasibility of implementing nationally agreed CAMHS referral criteria from the perspective of clinicians working in CAMHS in the North of Scotland. In addition, the study aimed to explore and gain consensus on possible factors which support clinicians working in specialist services. A three round electronic Delphi survey, an iterative structured process used to gather information and gain group consensus, was completed by twenty-eight clinicians working in CAMHS. Eight open ended questions in Round 1, were analysed using content analyses resulting in ninety-eight statements to be rated by the same group of clinicians in Round 2 and fifteen statements in Round 3. Of the ninety-eight statements, eighty-four reached consensus. Results indicate that the guidelines are viewed by many clinicians as both acceptable and important, however, implementation of the guidelines can present services with significant challenges and have highlighted the importance of services having the correct infrastructure before it is possible to implement the referral criteria in a consistent and meaningful way.
Keywords: borderline personality disorder; adolescents; group interventions; systematic review; Delphi study; service redesign